Antioxidant and Hypolipidemic Activity of Açai Fruit Makes It a Valuable Functional Food - Anna Virginia Adriana Pirozzi; Paola Imbimbo; Antonella D’Agostino; Virginia Tirino; Rosario Finamore; Daria Maria Monti; Renata Piccoli; Chiara Schiraldi (Antioxidants, 2020)
Several plant extracts are acquiring increasing value because of their antioxidant activity and hypolipidemic properties. Among them, great interest has been recently paid to açai fruit as a functional food. The aim of this study was to test the ability of açai extract in reducing oxidative stress and modulating lipid metabolism in vitro using different cell models and different types of stress. In fact, lipid peroxidation as evaluated in a HepG2 model was reduced five-fold when using 0.25 µg/mL of extract, and it was further reduced (20-fold) with the concentration increase up to 2.5 µg/mL. With the nonalcoholic fatty liver disease (NAFLD)in vitro model, all concentrations tested showed at least a two-fold reduced fat deposit. In addition, primary adipocytes challenged with TNF-α under hypoxic conditions to mimic the persistent subcutaneous fat, treated with açai extract showed an approximately 40% reduction of fat deposit. Overall, our results show that açai is able to counteract oxidative states in all the cell models analysed and to prevent the accumulation of lipid droplets. No toxic effects and high stability overtime were highlighted at the concentrations tested. Therefore, açai can be considered a suitable support in the prevention of different alterations of lipid and oxidative metabolism responsible for fat deposition and metabolic pathological conditions.